Democratic Republic of the Congo : Staff-Monitored Program and Request for Disbursement Under the Rapid Credit Facility; Press Release; Staff Report; and Statement by the Executive Director for the Democratic Republic of the Congo. (IMF Staff Country Reports; Country Report, 2020)
While macroeconomic policies in recent years have succeeded in restoring elements of macroeconomic stability under difficult circumstances, macroeconomic conditions are nonetheless precarious. The recent fall in commodity prices, new spending initiatives, and looser spending oversight during the political transition period have led to a weaker fiscal position mostly financed by the central bank. In that context, international reserves have fallen to critically low levels (one week of import coverage). Balance of payments needs remain both urgent and protracted.